Cultural processes in the Ukrainian SSR in Mykhaylo Demkovych-Dobriansky’s publications (1950s–1980s) - Кравець, Данило; Kravets, Danylo (Lviv Politechnic Publishing House, 2019)
На основі особового архівного фонду М. Демковича-Добрянського та його опублікованих робіт простежено ставлення автора до подій у радянській Україні 1950–1980-х рр. М. Демкович-Добрянський (1905–2003) – відомий історик, очільник української редакції радіо “Свобода” (1956–1972), публіцист та громадсько-політичний діяч, член Українського національно-демократичного об’єднання (УНДО) та голова Союзу українців у Великій Британії (СУВБ). Архів фондоутворювача зберігається у відділі рукописів ЛННБ України ім. В. Стефаника (фонд №298). Висвітлено життєвий і творчий шлях фондоутворювача, автора численних праць на тему українсько-польських та українсько-російських відносин; акцентовано увагу на радіопрограмах, які висвітлювали різні сторінки історії України: проблеми українсько-російських взаємин, історію, мову, аналіз феномену шістдесятників та дисидентів у СРСР тощо.

Presented paper is based on the Mykhaylo Demkovych-Dobriansky personal archive and it deals with his articles and radio programs devoted to cultural situation in the Soviet Ukraine (1950s–1980s). It focuses on his biography and intellectual heritage. M. Demkovych-Dobriansky was an author of hundreds radio programs on Radio Liberty and dozens of publications in different Ukrainian diaspora periodicals. His writings were dedicated to: Ukrainian-Russian relations (especially huge influence of Ukrainian scholars on Russian history), problems of Ukrainian culture in the Soviet Union (russification, lack of dictionaries and audio types with Ukrainian songs etc.), role of Ukrainian dissidents in the USSR (series of programs devoted to V. Chornovil, I. Dziuba etc.) etc.
Культурні процеси в Українській РСР у публікаціях Михайла Демковича-Добрянського (1950–1980-ті рр.)
Keywords: М. Демкович-Добрянський; радіо “Свобода”; діаспора; дисиденти; УРСР; культура; M. Demkovych-Dobriansky; Radio Liberty; diaspora; dissidents; Soviet Ukraine; culture; 821.1612-92Демкович-Добрянський.304.2(477)”195/198”